Cardiovascular ACE2 receptor expression in patients undergoing heart transplantation. (12th August 2021) - Bargehr, Johannes; Rericha, Patrick; Petchey, Alex; Colzani, Maria; Moule, Georgia; Malgapo, Marie Chet; Rassl, Doris; Tarkin, Jason; Mellor, Greg; Sampaziotis, Fotis; Brevini, Teresa; Gambardella, Laure; et al.
Abstract: Aims: Membrane‐bound angiotensin‐converting enzyme (ACE)2 is the main cellular access point for SARS‐CoV‐2, but its expression and the effect of ACE inhibition have not been assessed quantitatively in patients with heart failure. The aim of this study was to characterize membrane‐bound ACE2 expression in the myocardium and myocardial vasculature in patients undergoing heart transplantation and to assess the effect of pharmacological ACE inhibition. Methods and results: Left ventricular (LV) tissue was obtained from 36 explanted human hearts from patients undergoing heart transplantation. Immunohistochemical staining with antibodies directed against ACE2 co‐registered with cardiac troponin T (cTnT) and α‐smooth muscle cell actin (SMA) was performed across the entire cohort. ACE2 receptor expression was quantitatively assessed throughout the myocardium and vasculature. ACE2 was consistently expressed throughout the LV myocardium (28.3% ± 22.2% of cardiomyocytes). ACE2 expression was also detected in small calibre blood vessels (range, 2–9 μm), albeit at quantitatively much lower levels (5% ± 9% of blood vessels). There was no significant difference in ACE2 expression between patients receiving ACE inhibitors prior to transplantation and ACE inhibitor‐negative controls ( P  > 0.05). ACE2 expression did not differ significantly between the different diagnostic groups as the underlying reason for heart transplantation (ANOVA > 0.05). N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) ( R 2  = 0.37, P  = 0.0006) and pulmonary capillary wedge pressure (PCWP) ( R 2  = 0.13, P  = 0.043) assessed by right heart catheterization were significantly correlated with greater ACE2 expression in cardiomyocytes. Conclusions: These data provide a comprehensive characterization of membrane‐bound cardiac ACE2 expression in patients with heart failure with no demonstrable effect exerted by ACE inhibitors.